One‐Step Formation of Targeted Liposomes in a Versatile Microfluidic Mixing Device. Issue 7 (30th November 2022) - Shan, Han; Sun, Xin; Liu, Xin; Sun, Qi; He, Yao; Chen, Ziyan; Lin, Qibo; Jiang, Zixi; Chen, Xiang; Chen, Zeyu; Zhao, Shuang
Abstract: Targeted liposomes, as a promising carrier, have received tremendous attention in COVID‐19 vaccines, molecular imaging, and cancer treatment, due to their enhanced cellular uptake and payload accumulation at target sites. However, the conventional methods for preparing targeted liposomes still suffer from limitations, including complex operation, time‐consuming, and poor reproducibility. Herein, a facile and scalable strategy is developed for one‐step construction of targeted liposomes using a versatile microfluidic mixing device (MMD). The engineered MMD provides an advanced synthesis platform for multifunctional liposome with high production rate and controllability. To validate the method, a programmed death‐ligand 1 (PD‐L1)‐targeting aptamer modified indocyanine green (ICG)‐liposome (Apt‐ICG@Lip) is successfully constructed via the MMD. ICG and the PD‐L1‐targeting aptamer are used as model drug and targeting moiety, respectively. The Apt‐ICG@Lip has high encapsulation efficiency (89.9 ± 1.4%) and small mean diameter (129.16 ± 5.48 nm). In vivo studies (PD‐L1‐expressing tumor models) show that Apt‐ICG@Lip can realize PD‐L1 targeted photoacoustic imaging, fluorescence imaging, and photothermal therapy. To verify the versatility of this approach, various targeted liposomes with different functions are further prepared and investigated. These experimental results demonstrate that this method is concise, efficient, and scalable to prepare multifunctional targeted liposomal nanoplatforms for molecular imaging and disease theranostics. Abstract : A facile and scalable strategy is developed for one‐step construction of targeted liposomes using a microfluidic mixing device (MMD). The prepared Apt‐ICG@Lip realize PD‐L1 targeted in vivo photoacoustic imaging, fluorescence imaging, and photothermal therapy. The MMD offers a versatile platform to synthesize targeted nanoplatforms in one step, which has great potential in molecular imaging and cancer therapy.